The Comparative Effect of Particle Size and Support Acidity on Hydrogenation of Aromatic Ketones. Issue 19 (4th September 2019) - Kim, Kyung Duk; Wang, Zichun; Tao, Yongwen; Ling, Huajuan; Yuan, Yuan; Zhou, Cuifeng; Liu, Zongwen; Gaborieau, Marianne; Huang, Jun; Yu, Aibing
Abstract: A comparative study was reported for both the effects of shape‐confined cubic Pd particle size (8, 13, and 21 nm) and surface property of most commonly used supports (SiO2, Al2 O3, and silica‐alumina) on catalytic performance in the chemoselective hydrogenation of three model bio‐oil chemicals (benzaldehyde, acetophenone, and butyrophenone). The results showed that the size of Pd particles could be more associated with the hydrogenation reaction than acidities of the supports. Smaller size of Pd particles, regardless of the type of the support, provided the higher catalytic performance. XPS data showed that the electronic properties of Pd particles were similar, therefore, the possible reasons were the higher fraction of Pd atoms on corner in smaller particles, the lower accessibility of hydrogen atom to reactant on bigger particles, and the more low‐coordinated sites in the small‐size particles due to the short‐range ordering. In addition, Pd/SA catalysts (Brønsted acid sites on the support) showed the highest conversion and TOF compared to Pd/Al2 O3 and Pd/SiO2 catalysts. This might be due to the enhanced the diffusion rates of the chemicals on the surface of the catalysts although they could not induce the ionic effect from the metal surface. Pd/SiO2 catalysts performed better than Pd/Al2 O3 catalysts (Lewis acid sites on the support). The flexible SiOH groups on surface made the easy interaction with the metal particles and promote the reaction. Abstract : The shape‐confined cubic Pd particle size is more associated with the chemoselective hydrogenation than surface acidities of supports. Brønsted acid sites on the support promoted the highest conversion and TOF on Pd surface, while strong Lewis acid sites on the Al2O3 support cannot improve the activity of Pd catalysts.